Basic polymer engineering data - Rao, Natti S. (Hanser Publications, 2017)
Much more than a data reference, this book uses numerous examples to show how to apply basic design data to solve practical problems in polymer engineering. It offers both resin and up-to-date machine design data in a concise format and shows how resin-compatible polymer processing equipment can be designed by using easily understandable computational procedures based on thermodynamics and rheology. Basic design data for resins (mechanical, thermal, rheological, electrical, and optical properties), machines, parts, and processes is complemented by demonstrations of how to apply this data for application in extrusion, blown film, thermoforming, and injection molding. It is designed for simplicity, and all calculations can be carried out with a handheld calculator. With a practical and time-saving approach to problem-solving in plastics processing―which in many cases negates the need for complex, expensive software or databases―this book is a handy tool for beginners, practicing engineers, students, instructors in the field of plastics technology, and scientists from other fields with an interest in polymer engineering.--Provided by publisher.